2016
DOI: 10.1002/ecy.1497
|View full text |Cite
|
Sign up to set email alerts
|

Why do trees die? Characterizing the drivers of background tree mortality

Abstract: The drivers of background tree mortality rates-the typical low rates of tree mortality found in forests in the absence of acute stresses like drought-are central to our understanding of forest dynamics, the effects of ongoing environmental changes on forests, and the causes and consequences of geographical gradients in the nature and strength of biotic interactions. To shed light on factors contributing to background tree mortality, we analyzed detailed pathological data from 200,668 tree-years of observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
118
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 47 publications
9
118
1
3
Order By: Relevance
“…This group especially included trees that died because of high competition intensity, confirming that shading can suppress trees for a long period before they actually die (Abrams & Orwig, ). However, the effects of shading (and competition in general) and other stress factors frequently interact (Myers & Kitajima, ; Das et al ., ) and are difficult to disentangle in field settings.…”
Section: Discussionmentioning
confidence: 99%
“…This group especially included trees that died because of high competition intensity, confirming that shading can suppress trees for a long period before they actually die (Abrams & Orwig, ). However, the effects of shading (and competition in general) and other stress factors frequently interact (Myers & Kitajima, ; Das et al ., ) and are difficult to disentangle in field settings.…”
Section: Discussionmentioning
confidence: 99%
“…According to this algorithm, a tree will experience drought stress when the soil moisture drops below the water potential that would cause a 50% decline in hydraulic conductivity (Supporting information Table S2) for a period of 30 consecutive days. Leaf shed rate and drought stress duration parameters (Supporting information Figure S1) were selected, based on observations (Kelly, 2016) and comparisons of modeled and plot-level measurements of aboveground carbon in the Sierra Nevada Mountains, CA (Das, Stephenson, & Davis, 2016). Leaf shed rate and drought stress duration parameters (Supporting information Figure S1) were selected, based on observations (Kelly, 2016) and comparisons of modeled and plot-level measurements of aboveground carbon in the Sierra Nevada Mountains, CA (Das, Stephenson, & Davis, 2016).…”
Section: Modifications To the Community Land Modelmentioning
confidence: 99%
“…Previous studies have showed that large‐diameter trees comprise a large fraction of the biomass of many forests (Bastin et al, ; Brown et al, ; Clark & Clark, ; Lutz, Larson, Swanson, & Freund, ) and that they modulate stand‐level leaf area, microclimate and water use (Martin et al, ; Rambo & North, ). Large‐diameter trees contribute disproportionately to reproduction (van Wagtendonk & Moore, ), influence the rates and patterns of regeneration and succession (Keeton & Franklin, ), limit light and water available to smaller trees (Binkley, Stape, Bauerle, & Ryan, ), and contribute to rates and causes of mortality of smaller individuals by crushing or injuring sub‐canopy trees when their bole or branches fall to the ground (Chao, Phillips, Monteagudo, Torres‐Lezama, & Vásquez Martínez, ; Das, Stephenson, & Davis, ). Large‐diameter trees (and large‐diameter snags and large‐diameter fallen woody debris) make the structure of primary forests and mature secondary forests unique (Spies & Franklin, ).…”
Section: Introductionmentioning
confidence: 99%